Produção de anticorpos monoclonais anti-GITR e anti-CD25 através de cultivo de hibridomas e comparação do seu potencial como agentes antitumorais - Prampero, Anna Carolina (2017)
Nowadays, cancer is one of the most feared diseases, affecting each day more and more people worldwide. The importance of new cancer treatment researches is very clear since the ones that has been used are not very effective and may lead to drug resistance, implying in a constant dose increasing which can lead to toxicity issues. Collateral effects and the instability generated in the patient’s organism are also reasons why the necessity of discovering new cancer treatments is imminent. A treatment alternative that has aroused interest is the use of monoclonal antibodies as immunotherapics, since they act by stimulating the patient’s immune system neutralizing the tumor cells in a very efficient and specific way. This kind of antibody can be produced by culturing hybrid animal cells, better known as hybridoma, under strictly controlled conditions so they can be studied and used in human beings. For this reason, the major goal of this project was the production of murine monoclonal antibodies using hybridoma cell culture in order to stablish an efficient culture methodology for hybridomas PC-61 or DTA1 producers of monoclonal antibodies anti-CD25 and anti-GITR, respectively, with high quality and enough amounts using Fetal Bovine Serum (FBS) free medium to, in the future, carry out animal model studies of their potential as therapeutic agents for cancer treatment. Both hybridomas were cultivated on a small scale with RPMI medium and addition of SFB, for comparative purposes and only one was selcted for the second step. The sequential adaptation methodology test, consisted in a gradual percent’s reduction of medium with serum at the same time that increase the percentage of commercial medium without serum, and was selected the medium without SFB in which the hybridoma was better adapted. After was carried out on a laboratory scale in a system type spinner flask (500 ml) with the commercial medium selected in the previous step, in controlled conditions of temperature (37 ° C) and pH (7.2). Based on analyzes of cell culture results, amino acid consumption and monoclonal antibodies quantification , SFM commercial medium SFB-free provided better results for culturing the PC-61 hybridoma, allowing the pilot scale culture reached even higher cell densities than in the standard medium with addition of FBS.